Comparative Study of Different Brands of Furosemide Injection - Ruwida Kamour,; Jamal Elbakay, (AlQalam Journal of Medical and Applied Sciences, 2024)
Furosemide is one of loop diuretics which are very important drugs for treatment of hypertension and other medical problems. Parenteral furosemide is considered more effective than oral formulations; therefore, it is important to evaluate its therapeutic effectiveness starting from physicochemical properties. The aim of this study was to assess quality of five different brands of furosemide injection collected from different pharmacies in Tripoli-Libya. The five brands were tested for their alkalinity, ultraviolet wavelength maxima and content uniformity to assess if they comply with standards of BP2009. Manufacturing date was not printed in four samples. The pH of sample E was lower than accepted limit in addition to a low content of furosemide in sample D making it unacceptable. The results assured importance for parenteral products to comply with all physicochemical specifications as well as labelling. This would assure efficacy and safety of the drugs. يعتبر دواء الفيوروسيمايد نوع من أدوية المدرة للبول و التي تستعمل لعلاج ضغط الدم المرتفع و غيره من الأمراض. الحقن الوريدية للفيوروسيمايد هي الأكثر تأثيراً مقارنة بالمستحضرات الفموية و لذلك فإن من غاية الأهمية تقييم مدى فعاليته باجراء اختبارات فيزيائية و كيميائية. تهدف الدراسة لتقييم جودة خمسة منتجات دوائية لشركات مختلفة حيث تم تجميعها من صيدليات مختلفة بطرابلس – ليبيا. المنتجات الخمسة ثم اختبارهم من ناحية القاعدية، الامتصاص الطيفي للأشعة فوق البنفسجية، و تجانس المحتوى. و تقييم مدى مطابقتها مع مواصفات الدستور البريطاني. وجد أن تاريخ التصنيع لم يكن مكتوبا على ارلع منتجات. أيضا الرقم الهيدروجيني للعينة E كان أقل من المدى المذكور بالمرجع. وجد أن العينة D احتوت أقل كمية من الدواء و أقل من المطلوب مما جعلها مرفوضة . يجب أن تستوفي المنتجات الوريدية كامل المواصفات ابتداءا من الخصائص الفيزيائية الى المعلومات على المغلف و انتهاءا بمحتوى و تلركيز الدواء لضمان فعالية الدواء و ايضا عدم الضرر بصحة المريض